Crystalline damage in silicon wafers and 'rare event' failure introduced by low-energy mechanical impact. (1st June 2017) - Atrash, F.; Meshi, I.; Krokhmal, A.; Ryan, P.; Wormington, M.; Sherman, D.
Abstract: We used X-ray diffraction imaging to detect and characterize mechanical damage introduced to 300 mm silicon wafers by low impact energy exerted on the wafer edge. Maps of crystalline damage show a correlation between the damage size, the magnitude of the impact energy and the location of the impact point. We demonstrate the existence of crystalline non-visual defects; crystalline defects that appear in the X-Ray diffraction images but not in optical microscopy or scanning electron microscope. We propose a mechanism of crystalline damage formation at low impact energies based on finite element analysis and high-resolution synchrotron white beam transmission X-ray topography. Finally, we propose the concept of 'rare-event' to described relatively low rate of occurrence of wafer failure by fracture within semiconductor manufacturing facilities.